Kepemimpinan Dalam Lembaga Pendidikan Islam - Rusli Kembaren (Proceedings of Annual Conference on Islamic Educational Management, 2021)
: Leadership is the ability and readiness possessed by one to be able to influence, encourage, invite, guide, move and if necessary to compel others to accept that influence, and then to do something can help achieve specific objectives. Its inherent leadership relates to human energy, only in organized groups, and as a force or potential. In addition to the characteristics of a leader in the leadership of Islamic education, among others, it has sufficient knowledge and ability to control the institution or organization, enabling more privileges than others, understand the habits and language of the person responsible have a charism or authority before men or others, gently and affectionate to his subordinates, that others be sympathetic to him, deliberation with their followers and ask their opinions and experiences, have power and influence that can reign and prevent because a leader must control supervision over the work of the member, straighten the confusion, and invite them to do good and melt the evil, and be willing to hear Advice and not arrogant, because the advice of a sincere person.